Robotic resection of extrahepatic cholangiocarcinoma: Institutional outcomes of bile duct cancer surgery using a minimally invasive technique. Issue 2 (15th September 2021) - Sucandy, Iswanto; Shapera, Emanuel; Jacob, Kevin; Luberice, Kenneth; Crespo, Kaitlyn; Syblis, Cameron; Ross, Sharona B.; Rosemurgy, Alexander S.
Abstract: Background and Objectives: The purpose of this study is to report our early experience and outcomes, the first in North America, of Extrahepatic Cholangiocarcinoma (EHC) resection with Roux‐en Y Hepaticojejunostomy reconstruction via the robotic approach. Methods: With Institutional Review Board approval, 15 patients who underwent robotic resection of EHC were studied. Results: Patients were 74 (73 ± 8.9) years of age. There were 9 men and 6 women. Average body mass index was 24 (27 ± 6.3) kg·m −2 . Mean & Median ASA class was 3. Median Tumor size was 2 (2 ± 1.3) cm. There were no intraoperative complications. Operative duration was 453 (443 ± 85.0) minutes and the estimated blood loss was 150 (182 ± 138.4) ml. No patient required admission to the intensive care unit. Hospital length of stay was 4 (6 ± 3.2) days. There was one patient with Clavien‐Dindo Class 3 or greater complication. No mortality was seen in this series. Discussion: Robotic resection of EHC is safe, feasible, and reproducible with excellent clinical outcomes. Consequently, the robotic technique should be considered in some patients requiring EHC resection.